SOSIALISASI PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) UPAYA PENCEGAHAN RESIKO KECELAKAAN BAGI SISWA/I DI SMKN 1 PANTAI LABU KABUPATEN DELI SERDANG - Rizky Franchitika; Nurkhasanah Nurkhasanah; Soraya Muthma; M. Rizki; Dinnie Ananda Rizky; Alfiani Alfiani (Yayasan Nusa Cendekia Global, 2026)
Awareness of Occupational Safety and Health (K3) is a crucial aspect in the vocational education environment, especially in vocational high schools that have a high intensity of workshop practice. SMK Negeri 1 Pantai Labu is one of the educational institutions in Deli Serdang that prepares students to enter the industrial world. However, initial observations show that students still have a low understanding of the risk of work accidents and the use of standard Personal Protective Equipment (PPE). This service activity aims to increase the knowledge and awareness of students and educators about the importance of K3 culture. The methods used are socialization through material presentations, demonstrations of the use of PPE, and simulations of handling emergencies. The results of this activity showed an increase in participants' understanding by 85% based on post-test evaluation.